Postać Bedy Czcigodnego w polskim piśmiennictwie religijnym XVI–XVIII wieku - Puchalska-Dąbrowska, Bernadetta M. (Wydawnictwo Uniwersytetu Rzeszowskiego, 2014)
The aim of the article is to present Bede the Venerable as a role model present in the Polish religious prose of the 16th-18th centuries. The sources under discussion are mainly collections of the lives of saints. The profile of Bede, shown as a perfect Benedictine monk, scholar and priest is inspired by the earliest biographical Anglo-Saxon sources (e.g. Bede’s autobiography and Cuthbert’s letter on the hero’s death). Polish hagiography, following the directions of the Trent Council, aims at emphasizing Bede’s qualities required from the then clergy – in-depth spiritual life, thorough knowledge, respect towards authorities, and teaching skills.
Bede the Venerable as a Role Model in the Polish Religious Prose of the 16th-18th Centuries
Keywords: Beda Czcigodny; wzorce osobowe; proza religijna; hagiografia; źródła; Bede the Venerable; role model; religious prose; hagiography; sources